Аналіз використання штучного інтелекту для генерації розкладу занять і харчування дітей в закладах дошкільної освіти - Бондаренко, А. А.; Нестеренко, В. В.; Смєйко, Б. М. (ХНУРЕ, 2024)
This research examines a software tool designed for preschools to manage children's daily schedule and nutrition. Through artificial intelligence, specifically GPT which is a generative AI technology, this system enables teachers to create schedules adjusted to the needs of preschool groups and eating patterns, ensuring they get the right schedule and eating habits. Parents can easily see their children’s daily activities and meals, making it easier to stay informed about their well-being. The main purpose is to use this AI software to make the management of daily activities and nutrition in preschools more efficient and tailored to physical needs, enhancing both educational and health outcomes.
Keywords: AI; штучний інтелект; їжа; харчові плани; генерація розкладу